Innovation Management For Small-Scale Entrepreneurs In The Digital Era - Lapiti Gokmatua Sagala (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Innovation management is an important part of improving competitiveness for entrepreneurs, especially small-scale ones, who operate in the ever-evolving digital era. At present, there are still many small-scale entrepreneurs who still have not implemented management arrangements that can keep up with the times. At this time, it is certainly expected that all entrepreneurs can follow the trend, especially in financial management. This aims to increase efficiency and ease in processing data, both data financial and other data. The purpose of this study is to analyse how small-scale entrepreneurs can utilise innovation management to adapt to digital changes and improve their business performance. The method used in this research is a literature study and qualitative analysis by collecting data from various sources related to innovation management and the challenges faced by small-scale entrepreneurs. The sources of this research can be data collected from various valid sources and other scientific essays. The results show that small-scale entrepreneurs should be able to apply digital technology in their business processes, introduce innovations in products and services, and increase human resource capacity to support digital transformation. This research is expected to provide insights for small-scale entrepreneurs to utilise innovation management in facing the challenges of the digital era.